Russian forest sequesters substantially more carbon than previously reported - Schepaschenko, Dmitry; Moltchanova, Elena; Fedorov, Stanislav; Karminov, Victor; Ontikov, Petr; Santoro, Maurizio; See, Linda; Kositsyn, Vladimir; Shvidenko, Anatoly; Romanovskaya, Anna; Korotkov, Vladimir; Lesiv, Myroslava; et al. (Scientific reports, 2021)
Since the collapse of the Soviet Union and transition to a new forest inventory system, Russia has reported almost no change in growing stock (+ 1.8%) and biomass (+ 0.6%). Yet remote sensing products indicate increased vegetation productivity, tree cover and above-ground biomass. Here, we challenge these statistics with a combination of recent National Forest Inventory and remote sensing data to provide an alternative estimate of the growing stock of Russian forests and to assess the relative changes in post-Soviet Russia. Our estimate for the year 2014 is 111 ± 1.3 × 10 9 m 3 , or 39% higher than the value in the State Forest Register. Using the last Soviet Union report as a reference, Russian forests have accumulated 1163 × 10 6 m 3 yr -1 of growing stock between 1988–2014, which balances the net forest stock losses in tropical countries. Our estimate of the growing stock of managed forests is 94.2 × 10 9 m 3 , which corresponds to sequestration of 354 Tg C yr -1 in live biomass over 1988–2014, or 47% higher than reported in the National Greenhouse Gases Inventory.